2019
DOI: 10.1038/s41598-019-50654-7
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetic model of lead absorption and calcium competitive dynamics

Abstract: Lead is a naturally-occurring element. It has been known to man for a long time, and it is one of the longest established poisons. The current consensus is that no level of lead exposure should be deemed “safe”. New evidence regarding the blood levels at which morbidities occur has prompted the CDC to reduce the screening guideline of 10 μg/dl to 2 μg/dl. Measurable cognitive decline (reduced IQ, academic deficits) have been found to occur at levels below 10 μg/dl, especially in children. Knowledge of lead pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 106 publications
0
54
0
Order By: Relevance
“…The Pb capability to substitute for the calcium ions, allowing its passage across the blood-brain barrier and its accumulation in the brain via calcium-ATPase pumps 19 . Where the increasing in Pb intake may lead to the reduction of calcium steady state 34 . Consequently, both the peripheral and central nervous systems are disrupted 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pb capability to substitute for the calcium ions, allowing its passage across the blood-brain barrier and its accumulation in the brain via calcium-ATPase pumps 19 . Where the increasing in Pb intake may lead to the reduction of calcium steady state 34 . Consequently, both the peripheral and central nervous systems are disrupted 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Where the increasing in Pb intake may lead to the reduction of calcium steady state 34 . Consequently, both the peripheral and central nervous systems are disrupted 34 . This substitution may results in many neurological disorders including mental retardation, brain damage, behavioral problems, and may lead to several diseases like Alzheimer, Parkinson, and Schizophrenia 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal exposure to lead can cause several obstetric complications and adverse pregnancy outcomes [46]. Lead absorbed into the body, mainly by ingestion or inhalation, enters the bloodstream and accumulates in soft organs (mostly in brain, liver, and kidney) and bones [47,48]. It is considered that lead in bone represents approximately 95% of the total body burden in adults [47].…”
Section: Lead Exposure and Female Reproductive Healthmentioning
confidence: 99%
“…It is considered that lead in bone represents approximately 95% of the total body burden in adults [47]. During pregnancy, the demand of calcium rises, and lead stored in bone can replace the calcium and recirculate in the bloodstream, becoming an endogenous source of exposure [16,[48][49][50]. Lead from the blood can cross the placenta and impair the development of the fetus [51,52].…”
Section: Lead Exposure and Female Reproductive Healthmentioning
confidence: 99%
“…Pb and Cd exposure affects calcium metabolism in various ways. Furthermore, some studies suggested that calcium levels may have an impact on the blood lead levels [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%